Healthcare Use for Pain in Women Waiting for Gynaecological Surgery - Sarah Walker; Wilma M. Hopman; Meg E. Carley; Elizabeth G. Mann; Elizabeth G. VanDenKerkhof (Pain Research and Management)
Background. Pain while waiting for surgery may increase healthcare utilization (HCU) preoperatively. Objective. Examine the association between preoperative pain and HCU in the year prior to gynecological surgery. Methods. 590 women waiting for surgery in a Canadian tertiary care centre were asked to report on HCU in the year before surgery. Pain was assessed using the Brief Pain Inventory. Results. 33% reported moderate to severe pain intensity and interference in the week before surgery. Sixty-one percent (n=360) reported a total of 2026 healthcare visits, with 21% (n=126) reporting six or more visits in the year before surgery. After controlling for covariates, women with moderate to severe (>3/10) pain intensity/interference reported higher odds of overall HCU (≥3 pain-related visits to family doctor or specialist in the past year or ≥1 to emergency/walk-in clinic) compared to women with no or mild pain. Lower body mass index (BMI < 30 versus ≥30) and anxiety and/or depression were associated with emergency department or walk-in visits but not visits to family doctors or specialists. Conclusions. There is a high burden of pain in women awaiting gynecological surgery. Decisions about resource allocation should consider the impact of pain on individuals and the healthcare system.